Respiratory datasets: Use of READ Codes in the UK - a GPIAG project - Woodforde, C; Haughney, J; Thoonen, B; Walton, K; Levy, M (Primary care respiratory journal, 2002)
There is a need for agreed respiratory data entry codes for use in primary care; there are marked differences between codes used within and between different general practice computer systems. UK systems are based on READ Codes while the Dutch use ICPC codes in which only a small amount of information is systematically coded. The major advantage of the Dutch approach is its speed, as the time spent coding is limited to the essentials, while the UK READ codes are fairly comprehensive however these are not used systematically by many GPs and as a result, researchers and clinicians have difficulty comparing data drawn from primary care. With the establishment of the IPCRG, the primary care respiratory group of the ERS and the EUROPAD initiative, important steps towards international research collaboration have been taken. In the light of such initiatives internationally standardised data collection in General Practices may provide an extremely valuable source for disease management information. One possible solution involves the use of data entry templates utilizing agreed codes for different clinical situations. The GPIAG has initiated development of a comprehensive set of respiratory READ Codes to be categorized under the following headings: i) Minimum data set for codes which we would expect all doctors to enter when seeing patients with respiratory diseases and which would vary according to given situations; ii) an Extended data set for coding a wider range of respiratory consultation data, which would not necessarily be entered in every situation; iii) Maximum data set which would include all the available suggested codes for use and iv) those codes which should not be used for data entry.The Amsterdam conference will provide an opportunity for discussion of this important subject.